Fall-related injuries in a low-income setting: Results from a pilot injury surveillance system in Rawalpindi, Pakistan - Bhatti, Junaid A. (J Epidemiol Glob Health, 2015)
This study assessed the characteristics and emergency care outcomes of fall-related injuries in Pakistan. This study included all fall-related injury cases presenting to emergency departments (EDs) of the three teaching hospitals in Rawalpindi city from July 2007 to June 2008. Out of 62,530 injury cases, 43.4% (N = 27,109) were due to falls. Children (0–15 years) accounted for about two out of five of all fall-related injuries. Compared with women aged 16–45 years, more men of the same age group presented with fall-related injuries (50% vs. 42%); however, compared with men aged 45 years or more, about twice as many women of the same age group presented with fall-related injuries (16% vs. 9%, P < 0.001). For each reported death due to falls (n = 57), 43 more were admitted (n = 2443, 9%), and another 423 were discharged from the EDs (n = 24,142, 91%). Factors associated with death or inpatient admission were: aged 0–15 years (adjusted odds ratio [aOR] = 1.35), aged 45 years or more (aOR = 1.94), male gender (aOR = 1.15), falls occurring at home (aOR = 3.38), in markets (aOR = 1.43), on work sites (aOR = 4.80), and during playing activities (aOR = 1.68). This ED-based surveillance study indicated that fall prevention interventions in Pakistan should target children, older adult women, homes, and work sites.